Megye-reform – megyei tanács nélkül. Körzeti szolgáltatások a helyi-területi közigazgatásban - Vági, Gábor (Tér és Társadalom, 1989)
The system of local councils has to be replaced by a system of local govemments in the near future. Local governments of equal legal status would continue to be responsible for operating the so-called local public services (the provision of which is linked to the place of residencelike elementary school, panel doctor, and communal services). Therefore, they will need independent management, guaranteed shares from regional and national taxes, local taxes and state subsidy. But what about district services which should be provided for more than one seftlement (or more than a micro region of a few villages)? Since several (occasionaly several dozen) settlements are interested in using them, obviously, they should be maintained and financed in some joint form. But how to interpret that these are joint tasks? We have to ask the question: at which level of administration, in what scale and in what degree of aggregation is their joint provision conceived? There are several alternatives like (1) an institution is operated jointly by all local govemments concerned; (2) it is the responsibility of the central settlement but surrounding settlements contribute to the costs; (3) the ensemble of local governments of a functional urban region, or (4) of a county–or even a larger region–is the joint operator. The present paper argues that in Hungary district services should be provided by county-size units (Hungary is divided into 19 counties and the capital). If local governments are to be responsible for a new institution (e.g. secondary school) which serves them, financing would be full of conflicts and uncertain. It is extremely difficult to agree on the size and proportions of contributions on an annual basis. Moreover, the interests of settlements vary from year to year. Besides, in this way the money to be spent on school would not be decided within the budget of a local government but the money of the school would be cut off each local governmental budget concerned. Thereby also the use of money will be earmarked, i.e. determined. Similar difficulties will be encountered if the budget of the secondary school gets incorporated into the central settlement’s budget and the latter demands contribution from surrounding villages. Similar problems arise in case of functional regional joint operation when the service area is defined by the area served–again in an uncertain, annually changing way. Present Hungarian county sizes (300-600,000 inhabitants on average) facilitate an easier solution to the above problems. With the increase of scale via aggregation, the importance of borders decreases. The present paper argues that these ’counties’ should not function as an independent level of regional government but should be built up from the bottom as a union or an association is. The unique function of the association would be the operation of certain services (hospital, secondary school or home for the elderly). (This solution resembles the Danish county system.) The central government would give a general grant for the purposes of the association while its budget deficit would be covered from taxes collected by the local governments which form the association. Therefore, the association would not receive tax revenue on its own right and would not have the right to levy ’county taxes’ either. To build up such a system, the reform of the present organizational frameworks is needed–a transformation involving both recentralization and decentralization.